Assessment of penile erection methods in rhesus macaques to model pharmacokinetics of antiretroviral drugs and penile infection with simian immunodeficiency virus. Issue 1 (18th January 2016) - Hayes, James; Powell, Nathaniel; Lathrop, George; Heneine, Walid; Dobard, Charles W.
Abstract: Background: An established macaque model to assess HIV interventions against penile transmission is currently not available. Physiological changes during penile erections may affect susceptibility to infection and drug pharmacokinetics (PK). Here, we identify methods to establish erections in macaques to evaluate penile transmission, PK, and efficacy under physiologic conditions. Methods: Penile rigidity and length were evaluated in eight rhesus macaques following rectal electrostimulation (RES), vibratory stimulation (VS), or pharmacological treatment with Sildenafil Citrate (Viagra) or Alprostadil. Results: Rectal electrostimulation treatment increased penile rigidity (>82%) and length (2.5 ± 0.58 cm), albeit the response was transient. In contrast, VS alone or coupled with Viagra or Alprostadil failed to elicit an erection response. Conclusion: Rectal electrostimulation treatment elicits transient but consistent penile erections in macaques. High rigidity following RES treatment demonstrates increased blood flow and may provide a functional model for penile PK evaluations and possibly simian immunodeficiency virus (SIV) transmission under erect conditions.